Foaming Behavior and Pore Structure Evolution of Foamed Aluminum under the Extrusion Constraint. (22nd December 2020) - Wang, Lucai; Wang, Yanli; You, Xiaohong; Wang, Fang
Abstract : This study evaluates foaming behavior and pore structure evolution of aluminum foam by cross-sectional image processing, which was prepared by the powder compact melting (PCM) method under the constraint. The results revealed that the heating time and the heating rate are the key factors affecting the foaming behavior and pore structure of aluminum foam. The thermal decomposition of the foaming agent and aluminum melting behavior affect the foam expansion under different heating times and heating rates. The evolution of the pore structure during the foaming process includes pore formation, small-sized spherical pores, large-sized spherical pores, polygonal pores, merging, and collapse. Due to the limitation of the pipe wall, the maximum expansion height and porosity are constrained, and the macrostructure of aluminum foam is improved.